2022
DOI: 10.1093/nar/gkac615
|View full text |Cite
|
Sign up to set email alerts
|

Cap-independent translation and a precisely located RNA sequence enable SARS-CoV-2 to control host translation and escape anti-viral response

Abstract: Translation of SARS-CoV-2-encoded mRNAs by the host ribosomes is essential for its propagation. Following infection, the early expressed viral protein NSP1 binds the ribosome, represses translation, and induces mRNA degradation, while the host elicits an anti-viral response. The mechanisms enabling viral mRNAs to escape this multifaceted repression remain obscure. Here we show that expression of NSP1 leads to destabilization of multi-exon cellular mRNAs, while intron-less transcripts, such as viral mRNAs and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…It was suggested that SL1 specifically interact to Nsp1 via its unique structure and discharge the blockage of mRNA entry tunnel (Simeoni et al 2021 ). However, we showed that the integrity of secondary structure may not be absolutely needed for SL1 to mediate an escape from translational inhibition, in agreement with some recent studies that report poor structural relevance of SL1 to protein expression (Bujanic et al 2022 ; Slobodin et al 2022 ). Also, in these studies, they have found that the presence of specific C residues and the absence of G residues in SL1 are critical for sufficient protein expression, respectively, in spite of that the SL-like structure of the SL1 was mainly preserved in their mutagenesis experiments.…”
Section: Discussionsupporting
confidence: 92%
“…It was suggested that SL1 specifically interact to Nsp1 via its unique structure and discharge the blockage of mRNA entry tunnel (Simeoni et al 2021 ). However, we showed that the integrity of secondary structure may not be absolutely needed for SL1 to mediate an escape from translational inhibition, in agreement with some recent studies that report poor structural relevance of SL1 to protein expression (Bujanic et al 2022 ; Slobodin et al 2022 ). Also, in these studies, they have found that the presence of specific C residues and the absence of G residues in SL1 are critical for sufficient protein expression, respectively, in spite of that the SL-like structure of the SL1 was mainly preserved in their mutagenesis experiments.…”
Section: Discussionsupporting
confidence: 92%
“…RNA post-transcriptional modifications stand out as a basic mechanism of transcript and protein regulation [ 90 ]. SARS-CoV-2 interferes with this process in various ways; for example, NSP1 destabilizes a certain type of mRNA to evade antiviral proteins [ 91 ]. FBL is a protein responsible for RNA modification, with multiple possible important targets being down-regulated in critically ill individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of 5’-cap on genomic and sub-genomic SARS-CoV-2 mRNAs indicates the requirement of eIF4F for initiation of translation. Indeed, it was demonstrated that translation of sub-genomic SARS-CoV-2 mRNAs is cap-dependent and was shown to be highly sensitive to the eIF4E level (Slobodin et al, 2022). However, translation of genomic SARS-CoV-2 RNA does not require eIF4E and occurs in a cap-independent manner.…”
Section: Discussionmentioning
confidence: 99%